PROFIL PERESEPAN OBAT PADA PASIEN PENYAKIT JANTUNG RAWAT JALAN RS MITRA MEDIKA BONDOWOSO - Dewi Rashati; Muhammad Ibnu Maulana; Prima Soultoni Akbar (Jurnal Keperawatan Terapan, 2021)
The heart is the most important organ in the body, because there are no cells and tissues that can function properly without adequate oxygen and blood supply.This study aims to determine the percentage of drug use and the number of drugs used as a reference in the process of planning and drug procurement. Sampling was determined by total sampling technique. The sample used was 279 prescriptions for outpatient heart disease at Mitra Medika Bondowoso Hospital for the period March 2021.The results of research conducted on a sample of 279 prescriptions for outpatient heart disease patients at Mitra Medika Bondowoso Hospital for the period March 2021, based on the name of the most prescribed drug, 153 prescriptions for candesartan with a percentage of 14.35 percent, based on the number of drugs used. The most widely used was clopidogrel with a total usage of 4,231 tablets. Then based on the class of drugs the most prescribed was the diuretic group with 261 prescriptions with a percentage of 24.68 percent, based on the strength or dose of the drug the most widely used was clopidogrel with 144 prescriptions with a percentage of 13.51 percent.